A new topology and power control of grid-connected photovoltaic array. (24th October 2019) - Zhong, Li-Ping
Under the partial shading, the series photovoltaic modules will generate additional power loss and present a multi-peak power-voltage curve which brings difficulties to the maximum power point tracking. By using a novel grid-connected topology and power control method presented in this paper, the photovoltaic array can be connected through a full parallel structure and thus the shortcomings mentioned above can be overcome. A higher voltage, required for grid connection, also can be obtained through the topology without the need for any step-up transformer or boost circuit. Furthermore, the output power of the photovoltaic array can be adjusted by controlling the phase of the modulated wave. As result, the maximum power point tracking can be achieved with a simple method. The simulation and experiment results verified the validity of the proposed topology and control method.